A Systematic Literature Review on Global Treatment for Post-Poliomyelitis Syndrome - Nabilah, Aisyah; Ratu, Laverda Shauma; Cantika, Windy Cahya; Wardani, Ajeng Sayidah; Rahayuningrum, Indriyati Oktaviano (Universitas Muhammadiyah Surakarta, 2024)
Abstract Introduction: Polio can lead to Post-Poliomyelitis Syndrome (PPS) due to the long-term effects of poliovirus on motor neurons. After poliomyelitis's initial recovery, patients may experience neuromuscular symptoms 15 years post-infection. Polio survivors often deal with residual muscle atrophy and joint problems, acute flaccid paralysis, postural deformities, and respiratory muscle weakness. There are various rehabilitative treatments to manage PPS, including occupational therapy, exercise, medications, and surgery that shown effectiveness in improving patients' mobility and QoL. Purpose: This study aims to identify and evaluate the effectiveness of various global treatment strategies for Post-Poliomyelitis Syndrome. Methods: This study adheres to Cochrane Collaboration's methodological guidelines for literature reviews. Five databases were utilized, guided by PICO (Population, Intervention, Control, Outcome) framework. The inclusion criteria specified original articles published in English between 2020-2024, with full-text availability. Data regarding treatment outcomes were synthesized, leading to the formulation of conclusions. Results and Discussion: The search obtained 2040 studies, and 1835 abstracts were reviewed. Following full-text assessment, 187 papers were examined, and 19 studies were included. Most of the studies had an RCT design in outpatient setting. Interventions with self-management programs, Hinge-Knee Replacement (HKR), interactive videogame exercises, Radio Electric Asymmetric Conveyer (REAC), Whole-Body Vibration (WBV), Total-Knee Arthroplasty (TKA), and Knee-Ankle-Foot Orthoses (KAFO) showed significant results (p<0.005). While L-citrulline supplementation and PVP-lavage intervention showed no significant effect with post-polio syndrome. Conclusion: This research highlights the significance of tailored healthcare management of PPS according to the patient's severity, offering a variety of approaches that can improve the patient's QoL and independence.